The dynamic effects of monsoon rainfall shocks on agricultural yield, wages, and food prices in India - Björn Brey; Matthias S. Hertweck (The Scandinavian Journal of Economics, 2023)
This paper shows that, first, the effects of monsoon rainfall shocks on agricultural yield in India are highly asymmetric: yield falls strongly after droughts, whereas excessive rainfall has only little effects. Second, our key novel finding is that the short-lived yield loss after a widespread drought elicits a persistent decline (increase) in wages (food prices), which lasts for up to five years. Third, affiliation to the same National Sample Survey region (and thus to the same state) seems to be a key determinant of internal migration, whereas distance appears more relevant for food arbitrage trading.
Keywords: 330; Agricultural yield; food prices; rainfall shocks; wages